Asuhan Kebidanan Komprehensif Pada Ny. K Umur 29 Tahun Dengan Kekurangan Energi Kronik (KEK), Skoliosis Badan dan Tinggi Badan Kurang Dari 140 Cm Di Wilayah Kerja Puskesmas Paguyangan Kec.Paguyangan Kabupaten Brebes Tahun 2023 - Sinta Wati; Hafsah Hafsah; Nur Hidayah (Pusat Riset dan Inovasi Nasional, 2024)
According to the World Health Organization (WHO), in 2022, the maternal mortality rate (MMR) in Central Java is 98.6 cases, while the infant mortality rate (IMR) is 8.30/1000 live births. Paguyangan Community Health Center is the center of Brebes Regency in Central Java which contributed 1 case of MMR and 1 case of IMR. One of the reasons for this is Chronic Energy Deficiency (KEK), and a height of less than 140 cm, which occurs during pregnancy. One of the efforts to reduce MMR and IMR is by providing comprehensive midwifery care with a continuity of care approach. The aim of this research is to implement comprehensive midwifery care services starting with pregnant women, giving birth, new-borns, postpartum and family planning.